Risk factors for insufficient weight and height gain in children with congenital heart disease followed up at a nutrition outpatient clinic - Beatriz Cassaniga Talassi; Tulio Konstantyner; Stela de Almeida Miranda; Heitor Pons Leite (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: To describe weight and height evolution and to identify risk factors for insufficient anthropometric growth in children with congenital heart disease. Methods: Historical cohort study including 131 children with congenital heart disease, followed up at a nutrition outpatient clinic. The anthropometric indices over time (initial score, after 12 and 24 months of follow-up) were analyzed using generalized estimating equations. The outcome was 'insufficient weight-height gain', defined as an increase of ≤0.5 in the z-score of weight-for-age (W/A), height-for-age (H/A) or body mass index-for-age (BMI/A) after 12 months of follow-up. Multiple logistic regression models were applied to identify risk and confounding factors. Results: The z-scores of W/A (p<0.001) and BMI/A (p<0.001) improved after 12 months, as well as the three indexes after 24 months (p<0.001). At the end of this period, 55.7% of the patients did not achieve an increase of >0.5 in the Z score of W/A; 77.1%, of H/A; and 45.8%, of BMI/A. A follow-up of less than five appointments was associated with insufficient gain in W/A (OR 7.78; 95%CI 3.04-19.88), H/A (OR 10.79; 95%CI 2.22-52.45) and BMI/A (OR 2.54; 95%CI 1.12-5.75). Not having undergone cardiac surgery and being aged ≥12 months were factors associated with insufficient W/A gain (OR 3.95; 95%CI 1.38-11.29/OR 3.60; 95%CI 1.33-9.72) and BMI/A (OR 2.81; 95%CI 1.08-7.28/OR 3.39; 95%CI 1.34-8.56). Low income was associated with insufficient H/A gain (OR 4.11; 95%CI 1.25-13.46). Conclusions: Being aged less than or 12 months, the lowest number of appointments, absence of surgical treatment and low family income were risk factors for insufficient weight and height gain in children with congenital heart disease.